2011
DOI: 10.1007/s10549-011-1612-1
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for biological effects of metformin in operable breast cancer: a pre-operative, window-of-opportunity, randomized trial

Abstract: , Colin Purdie, Susan Bray, et al.. Evidence for biological effects of metformin in operable breast cancer: a pre-operative, window-of-opportunity, randomized trial. Breast Cancer Research and Treatment, Springer Verlag, 2011, 128 (3) AbstractMetformin may reduce the incidence of breast cancer and enhance response to neoadjuvant chemotherapy in diabetic women. This trial examined the effects of metformin on Ki67 and gene expression in primary breast cancer.Non-diabetic women with operable invasive breast canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
211
2
6

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 264 publications
(225 citation statements)
references
References 30 publications
6
211
2
6
Order By: Relevance
“…Overall, these prospective, preoperative window studies in breast cancer (62,64,65), despite reservations about trial design and methodology, demonstrate that metformin is safe for women with primary breast cancer and confirm the attraction of metformin as a therapeutic agent.…”
Section: Metformin and Breast Cancer Trialsmentioning
confidence: 67%
See 1 more Smart Citation
“…Overall, these prospective, preoperative window studies in breast cancer (62,64,65), despite reservations about trial design and methodology, demonstrate that metformin is safe for women with primary breast cancer and confirm the attraction of metformin as a therapeutic agent.…”
Section: Metformin and Breast Cancer Trialsmentioning
confidence: 67%
“…The first randomized clinical trial using metformin (1,000 mg bd) in breast cancer was reported in 2011 and used the preoperative window-of-opportunity setting (62). This novel trial randomized patients to receive metformin for 2 weeks or watchful waiting for 2 weeks between diagnostic biopsy and definitive surgery.…”
Section: Metformin and Breast Cancer Trialsmentioning
confidence: 99%
“…Reports have indicated that metformin reduced cancer incidence (38,39). Metformin also reduced proliferative output of breast cancer cells in nondiabetic cancer patients (40). These interesting findings highlight an interesting dilemma-is energy or REDOX homeostasis more important for cancer survival?…”
Section: Discussionmentioning
confidence: 93%
“…Hyperinsulinemia, insulin resistance (IR) [7,8,10], and enhanced levels of insulin-like growth factor-1 (IGF-1) [11] have all been proposed as the underlying causative mechanisms, mainly on the basis of in vitro and animal studies supporting a role for insulin, insulin receptor, and IGFs in BC initiation [12][13][14] and progression [15]. These experimental findings are strengthened by indirect observations that metformin, a biguanide oral hypoglycemic agent capable of lowering insulin levels and improving IR, also might The Oncologist 2016;21:1041-1049 www.TheOncologist.com ©AlphaMed Press 2016 be effective in reducing BC incidence [8] and may beneficially act on proliferation and apoptosis markers in early BC stages [16][17][18]. Accordingly, metformin is being investigated in an adjuvant trial investigating invasive cancer-free survival in nondiabetic women with early breast cancer (National Cancer Institute of Canada Clinical Trials Group MA.32); the primary outcome measure is expected to be released late in 2017 [19].…”
Section: Introductionmentioning
confidence: 99%